2016
DOI: 10.1161/atvbaha.116.308039
|View full text |Cite
|
Sign up to set email alerts
|

Significant Differences in Antigen-Induced Transendothelial Migration of Human CD8 and CD4 T Effector Memory Cells

Abstract: Objective Circulating human T effector memory cell (TEM) recognition of non-self MHC molecules on allograft endothelial cells (EC) can initiate graft rejection despite elimination of professional antigen presenting cells necessary for naïve T cell activation. Our prior studies of CD4 TEM have established that engagement of the T cell receptor (TCR) not only activates T cells but also triggers transendothelial migration (TEM) by a process that is distinct from that induced by activating chemokine receptors (CR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Atherosclerosis is a complex inflammatory disease of medium and large-sized arteries, in which three cellular types are mainly involved, including endothelial cells, macrophages, and smooth muscle cells 25 27 . The pathophysiologic mechanisms by which nicotine promotes vascular diseases particularly atherosclerosis is manifold and complex.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis is a complex inflammatory disease of medium and large-sized arteries, in which three cellular types are mainly involved, including endothelial cells, macrophages, and smooth muscle cells 25 27 . The pathophysiologic mechanisms by which nicotine promotes vascular diseases particularly atherosclerosis is manifold and complex.…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture experiments using superantigen have revealed that both CD4+ and CD8+ T EM that recognize antigens on the apical surface of human microvascular ECs are induced to transmigrate through the EC barrier ( 66 ). Morphologically, the initial T cell response to antigen recognition on ECs appears similar to that which occurs during antigen presentation by professional APCs.…”
Section: Antigen Presentation By Ecsmentioning
confidence: 99%
“…During TCR-triggered transendothelial migration, CD4+ T EM discharge granules, releasing granzyme A, the proteolytic activity of which is required for effective transmigration ( 67 ). In contrast, CD8+ T EM transits through the EC monolayer without discharging their granules, which contain granzyme B and perforin in addition to granzyme A ( 66 ). The basis for this difference in granule release is unknown but protects EC from lysis.…”
Section: Antigen Presentation By Ecsmentioning
confidence: 99%
“…[4][5][6] This, in addition to the accumulation of cholesterol and smooth muscle cells (SMCs) in the intima, leads to the transformation of monocytes into foam cells, which consume dead cells and lipids. [7][8][9] The atherogenic process involves multiple cell types, that is, endothelial cells (ECs), 10 SMCs, 11 immune cells, 12 and stem/progenitor cells, 13 in which levels of both intracellular and extracellular reactive oxygen and nitrogen species play a fundamental role in vascular cell homoeostasis and eventually affects the development of atherosclerosis.…”
mentioning
confidence: 99%